2022
DOI: 10.1186/s13052-022-01280-z
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary neuropathy with liability to pressure palsies (HNPP): Intrafamilial phenotypic variability and early childhood refusal to walk as the presenting symptom

Abstract: Background Limping and/or refusal to walk is a common complaint in the setting of the pediatric department, with a widely diverse differential diagnosis. An unusual etiology, is that of a hereditary neuropathy. Hereditary neuropathy with liability to pressure palsies (HNPP) is a recurrent, episodic demyelinating neuropathy, most commonly caused by a 17p11.2 chromosomal deletion encompassing the PMP22 gene. Methods We pursued chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Karlinsky et al [180] reported their experience about an unusual case of hereditary neuropathy with liability to pressure palsies (HNPP) who had limping as a major presenting symptom. HNPP is an autosomal dominant disease characterized by recurrent, episodic demyelinating neuropathy caused by 17p11.2 chromosomal deletion encompassing the PMP22 gene.…”
Section: -Pressure Palsiesmentioning
confidence: 99%
“…Karlinsky et al [180] reported their experience about an unusual case of hereditary neuropathy with liability to pressure palsies (HNPP) who had limping as a major presenting symptom. HNPP is an autosomal dominant disease characterized by recurrent, episodic demyelinating neuropathy caused by 17p11.2 chromosomal deletion encompassing the PMP22 gene.…”
Section: -Pressure Palsiesmentioning
confidence: 99%